Clinically decisive (dis)agreement in multidisciplinary team assessment of esophageal squamous cell carcinoma; a prospective, national, multicenter study. (2nd September 2021) - Achiam, Michael Patrick; Nordsmark, M.; Ladekarl, M.; Olsen, A.; Loft, A.; Garbyal, Rajendra Singh; Larsen, M. H.; Ainsworth, A. P.; Kristensen, T. S.; Dikinis, S.; Kjær, D. W.; Bæksgaard, L.; et al.
Abstract: Background: Decisions regarding tumor staging, operability, resectability, and treatment strategy in patients with esophageal cancer are made at multidisciplinary team (MDT) conferences. We aimed to assess interobserver agreement from four national MDT conferences and whether this would have a clinical impact. Methods: A total of 20 patients with esophageal cancer were included across all four upper gastrointestinal (GI) cancer centers. Fully anonymized patient data were distributed among the MDT conferences which decided on TNM category, resectability, operability, curability, and treatment strategy blinded to each other's decisions. The interobserver agreement was expressed as both the raw observer agreement and with Krippendorff's α values. Finally, a case-by-case evaluation was performed to determine if disagreement would have had a clinical impact. Results: A total of 80 MDT evaluations were available for analysis. A moderate to near-perfect observer agreement of 79.2%, 55.8%, and 82.5% for TNM category was observed, respectively. Substantial agreement for resectability and moderate agreement for curability were found. However, an only fair agreement was observed for the operability category. The treatment strategies had a slight agreement which corresponded to disagreement having a clinical impact in 12 patients. Conclusions: Esophageal cancer MDT conferences had an acceptable interobserver agreement on resectability and TM categories; however, the operability assessment had a high level of disagreement. Consequently, the agreement on treatment strategy was reduced with a potential clinical impact. In future MDT conferences, emphasis should be on prioritizing the relevant information being readily available (operability, T & M categories) to minimize the risk of disagreement in the assessments and treatment strategies, and thus, delayed or suboptimal treatment.